Infection control practices employed within small animal veterinary practices—A systematic review. (31st May 2019) - Willemsen, Angela; Cobbold, Rowland; Gibson, Justine; Wilks, Kathryn; Lawler, Sheleigh; Reid, Simon
Abstract: Effective infection control (IC) provides a safe environment for staff, clients and animals of veterinary practices by reducing the risk of nosocomial and zoonotic infections, which are associated with increased hospital stays, costs, morbidity and mortality. An equally important issue arising from nosocomial infection is the loss of trust between the client and the veterinary practice that has potential negative impacts on the veterinary practice in terms of economic risk and the well‐being of staff. Furthermore, an emerging and significant threat, in this context, is antimicrobial resistance. The aim of this systematic review was to critically review published reports that documented current IC practices and evaluated interventions to improve IC practices. A systematic literature search using ten databases to identify papers published over a 20‐year period (February 1996 to February 2016) was conducted for studies that met the inclusion criteria. Included studies were assessed using the PRISMA and STROBE‐Vet statements. A total of 14 of 1, 615 identified studies met our inclusion criteria. Infection control practices included hand hygiene, sharps handling, environmental cleaning, personal protective equipment and personnel vaccination. Descriptive studies were the predominant research design for assessing IC compliance. Only three studies were interventions. Compliance with IC protocols was poor and only marginally increased with multimodal educational campaigns. There was significant variation in the implementation of IC by veterinary staff. Workplaces that had IC policies, management support and a staff member supporting their implementation were more likely to embrace good IC. Infection control data in veterinary practices were inconsistently reported and collected. Clearly defining IC and determining prevalence of these practices within the veterinary field is important given the limited research in this area. Further, developing and implementing educational campaigns for this sector is needed.